Studi sensitasi baja tahan karat tipe 316 sebagai bahan kelongsong dan struktur fast breeder reactors - Maman Kartaman A.; Rosika Kriswarini; Dian Anggraini (Jurnal Teknologi Bahan Nuklir, 2015)
Abstract Sensitization study of type-316 stainless steell as cladding and structure of fast breeder reactor. Stainless steel was used in nuclear industry as cladding of Liquid Metal Fast Breeder Reactor (LMFBR), which operation temperature above 500 0C. According to the theory, resistance of stainless steel type 316 is good enough, but in the high temperature tend to influence by intergranular corrosion. The sensitization degree of Stainless Steel type 316 ( SS 316 ) was calculated by potentiostat using potentiodynamic method, and was observed by scanning electron microscope ( SEM ). The objective of this research was to analized the effect of heat treatment on corrosion resistance. First, samples were heat treated at 1,000°C for 3 hours and then were quenched in the water for 30 minutes. Samples were heat treated for 6 hours on the temperature : 350, 450, 550, and 650°C. The heat treated samples were corrosion tested by Potensiostat model M 273 with Potensiodynamic method. The surface of samples were observed by scanning Electron Microscope. Three kinds of SS 316 samples : Blank, solution treatment, and ageing for 650oC  were characterized by X – ray diffractor. The result showed that the corrosion rates increased with the increasing temperature. The corrosion rate of samples heat treated at 550 and 650°C were 105,9 and 118.37 mpy, the samples were heat treated at 350 and 450 °C after solution treatment did not exhibit intergranular, corrosion rate respectively were 89,39 and 91,06 mpy. The corrosion rates of samples that were heat treated at 550°C and 650°C without solution treatment, revealed were higher than with solution treatment. Keywords : inter granular corrosion, austenitic stainless steel type of 316, sensitization Abstrak Studi sensitasi baja tahan karat tipe 316 sebagai bahan kelongsong dan struktur fast breeder reactors. Dalam industri nuklir, baja tahan karat, paduan alumunium dan zirkaloy digunakan sebagai komponen pendukung reaktor riset atau daya dalam bentuk tangki bertekanan, pipa, kelongsong, bahan struktur dan lain – lain. Baja tahan karat tipe 316 dan 316L digunakan sebagai kelongsong bahan bakar LMFBR dimana temperatur operasinya bisa mencapai sekitar 500 0C. Temperatur operasi yang tinggi akan mengakibatkan fenomena sensitasi, yaitu fenomena dimana baja tahan karat menjadi rentan terhadap serangan korosi terutama korosi batas butir. Oleh karena itu dilakukan penelitian untuk mengetahui sejauh mana pengaruh panas terhadap ketahanan korosinya. Sampel SS 316 terlebih dahulu diberi perlakuan panas dari suhu 350 hingga 650 0C, selanjutnya diuji korosi menggunakan metode potensiodinamik. Hasilnya menunjukkan bahwa laju korosi sampel SS 316 yang telah dilaku panas yaitu solution treatment pada suhu 1000 0C dan diikuti artificial aging pada suhu 350, 450, 550 dan 650 0C berturut-turut adalah 56,59 mpy, 89,39 mpy, 91,06 mpy ; 105,9 mpy dan 118,37 mpy. Semakin tinggi suhu aging terlihat laju korosinya semakin tinggi. Pada mikrograf sampel SS 316 yang diamati menggunakan mikroskop elektron (SEM) menunjukkan telah terjadi korosi yang cukup signifikan pada bahan yang telah di aging pada suhu 550 dan 6500C. Pola difraksi untuk sampel SS 316 yang dilaku panas solution treatment dan diiukuti aging suhu 650oC menunjukkan terjadi perubahan fasa yaitu fasa kedua atau senyawa intermetalik yang menyebabkan laju korosi sampel SS 316 menjadi relatif tinggi. Kata Kunci : korosi batas butir, baja tahan karat SS 316, sensitasi